Hadith #2345 - Sunan Abi Dawud - Abdullah bin Swad'h عبد الله بن سوادة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Samra bin Jundub (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: How good is the believers meal of dates shortly before dawn.
Grade: Sahih